2013
DOI: 10.1104/pp.113.220608
|View full text |Cite
|
Sign up to set email alerts
|

PYR/RCAR Receptors Contribute to Ozone-, Reduced Air Humidity-, Darkness-, and CO2-Induced Stomatal Regulation      

Abstract: Rapid stomatal closure induced by changes in the environment, such as elevation of CO2, reduction of air humidity, darkness, and pulses of the air pollutant ozone (O3), involves the SLOW ANION CHANNEL1 (SLAC1). SLAC1 is activated by OPEN STOMATA1 (OST1) and Ca2+-dependent protein kinases. OST1 activation is controlled through abscisic acid (ABA)-induced inhibition of type 2 protein phosphatases (PP2C) by PYRABACTIN RESISTANCE/REGULATORY COMPONENTS OF ABA RECEPTOR (PYR/RCAR) receptor proteins. To address the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
232
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(252 citation statements)
references
References 70 publications
14
232
5
Order By: Relevance
“…These data suggest a greater flexibility and faster stomatal responsiveness to changes in vapor pressure deficit (VPD) in angiosperms. This could be expected, as the responses to changes in VPD are linked with the biosynthesis and presence of ABA (Bauer et al, 2013;McAdam and Brodribb, 2015) as well as ABA signaling (Merilo et al, 2013), and stomatal ABA responses in angiosperms are faster and stronger than in ferns (Brodribb and McAdam, 2011; Fig. 1, B and C).…”
Section: Stomatal Responses To Subambient and Above-ambient Co 2 Concmentioning
confidence: 96%
See 1 more Smart Citation
“…These data suggest a greater flexibility and faster stomatal responsiveness to changes in vapor pressure deficit (VPD) in angiosperms. This could be expected, as the responses to changes in VPD are linked with the biosynthesis and presence of ABA (Bauer et al, 2013;McAdam and Brodribb, 2015) as well as ABA signaling (Merilo et al, 2013), and stomatal ABA responses in angiosperms are faster and stronger than in ferns (Brodribb and McAdam, 2011; Fig. 1, B and C).…”
Section: Stomatal Responses To Subambient and Above-ambient Co 2 Concmentioning
confidence: 96%
“…Thus, as in experiments with ABA, growth in the growth room with lower RH tended to reduce the stomatal sensitivity in D. filix-mas and A. filix-femina. As stomatal responses to CO 2 are tightly coupled with ABA responses (Xue et al, 2011;Merilo et al, 2013;Chater et al, 2015), the analogous dampening of responses to ABA and elevated CO 2 found in A. filix-femina and D. filix-mas when grown at low RH suggests that the underlying mechanisms responsible for the effect of growth conditions could be similar and potentially related to ABA levels.…”
Section: Stomatal Responses To Subambient and Above-ambient Co 2 Concmentioning
confidence: 99%
“…The dominant role for SnRK2s in this ABA signaling cascade is strongly supported by experimental data. The phenotype of single gene mutants in the key SnRK2 for stomatal responses to ABA, OST1, are profound, displaying no sensitivity to ABA (Mustilli et al, 2002) or VPD (Merilo et al, 2013;Merilo et al, 2015). While other SnRK2-independent signaling pathways for ABA perception and SLAC activation have been suggested (Geiger et al, 2010;Brandt et al, 2012;Pornsiriwong et al, 2017), these are redundant and many either converge or require cross-talk with functional OST1 to activate anion channels (Brandt et al, 2015).…”
Section: Co-option Of An Ancient and Highly Conserved Aba Signaling Pmentioning
confidence: 99%
“…In angiosperms, however, ABA biosynthesis is extremely rapid (Christmann et al, 2005;Waadt et al, 2014; and can be up-regulated by a drop in leaf turgor over the time frame of minutes (Pierce and Raschke, 1981;. Thus, angiosperms respond to VPD using ABA, as is evidenced by the change in ABA levels in angiosperm leaves in response to step changes in VPD (Bauerle et al, 2004;, while mutants in ABA biosynthetic and signaling genes have compromised stomatal responses to VPD (Xie et al, 2006;Merilo et al, 2013;. The result of this regulation of stomatal responses to VPD by ABA is that, unlike all other vascular land plant clades, the stomatal response to VPD in angiosperms is often hysteretic and unable to be predicted by passive hydraulic processes (O'Grady et al, 1999;.…”
Section: Diversity In the Regulation Of Water Use Among Seed Plants Imentioning
confidence: 99%
“…Elevated CO 2 concentration activates anion channels, resulting in depolarization of plasma membrane in guard cells, causing efflux of solutes and stomatal closure [7][8][9][10] . Earlier studies in Arabidopsis identified several mutants with defects in CO 2 -induced stomatal movements [11][12][13][14][15][16][17][18][19] . However, most of these mutants including abi1-1, abi2-1, gca2, ost1 and slac1 were insensitive to both CO 2 and abscisic acid (ABA), representing components shared by both signalling pathways 5,20 .…”
mentioning
confidence: 99%